Proposed new interior design of Skateline One - Stop Training Centre at Lot 2395, Seksyen 41, Jalan Sultan Ismail, Bandaraya Kuala Lumpur for Eco Sports Malaysia Sdn. Bhd / Muhammad Syazwan Fitri Ahmad Zama - Ahmad Zama, Muhammad Syazwan Fitri (Faculty of Architecture, Planning and Surveying, 2012)
The final project of interior design for diploma is the manifestation to students’ understanding on process aspects of interiordesign that has been studied from the basic to presentation level of design proposal. The project that I choose for my final year project is design a new interior design of Skateline One-Stop Training Centre at lot 2395, Seksyen 41, Jalan Sultan Ismail Bandaraya Kuala Lumpur. This centre will operate as an official training centre for Malaysia skates and few other nearest country neighborhood skates such as Singapore. The Centre aim is for the skates would like to come for a training sessions and practices and also provide shop skate for customer who would like to upgrade and services their skate, new beginner skates would like to learn a proper skates lesson and tricks and also customer or visitor who like to buy a skates merchandises as gift. Due to the wide range of skates and customers come from all different backgrounds, races and countries to the Skateline, the concept and style for the centre must be suitable to each individual and must be comfortable to each skaters and customers that's shop in the Skateline. The image and concept that has been choose not only must be suitable to the skaters, but also must be able to give a positive effect and confident to the skaters to skate. Therefore, the style I choose for the Skateline new interior scheme is 'Urban Street Style' which bring the meaning of design concerns the arrangement, appearance and functionality of towns and cities, and in particular the shaping and uses of urban public space freedom which not complementary with a certain group or races. It is about the freedom and unites with others as one. However, to achieve a good final design, a few research has to be done where the research purpose is to identify the client background and the Skateline skaters aim's, the type of activity that is always be in customer attention, kind of space planning that should be in the centre, type of services and facilities that will provide in there, time the business operation start, and others information that is complementary with centre operation system. The type of research that has been taken in this project is by interview, newspaper, internet, observation, experience and case study. Finally, a complete design of proposal will be produce. It consists of project brief, concept and images, site analysis, building analysis, systematic design, layout plan, section, elevation, design detail, furniture design proposal, a complete models structure, axonometric, three dimensional view (3D) and sample board.